Implementation of colorectal cancer screening interventions in low-income and middle-income countries: a scoping review protocol. Issue 6 (11th June 2020) - Schliemann, Désirée; Matovu, Nicholas; Ramanathan, Kogila; Muñoz-Aguirre, Paloma; O'Neill, Ciaran; Kee, Frank; Su, Tin Tin; Donnelly, Michael
Abstract : Introduction: Colorectal cancer (CRC) imposes a significant global burden of disease. CRC survival rates are much lower in low-income and middle-income countries (LMICs). Screening tends to lead to an improvement in cancer detection and the uptake of available treatments and, in turn, to better chances of cancer survival. Most evidence on CRC screening interventions comes from high-income countries. The objective of this scoping review is to map the available literature on the implementation of CRC screening interventions in LMICs. Methods and analysis: We will conduct a scoping review according to the framework proposed by Arksey and O'Malley (2005). We will search MEDLINE, EMBASE, Web of Science and Google Scholar using a combination of terms such as "colorectal cancer", "screening" and "low-middle-income countries". Studies of CRC screening interventions/programmes conducted in the general adult population in LMICs as well as policy reviews (of interventions in LMICs) and commentaries on challenges and opportunities of delivering CRC screening in LMICs, published in the English language before February 2020 will be included in this review. The title and abstract screen will be conducted by one reviewer and two reviewers will screen full-texts and extract data from included papers, independently, into a data charting template that will include criteria from an adapted template for intervention description and replication checklist and implementation considerations. The presentation of the scoping review will be reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension for Scoping Reviews guidance. Ethics and dissemination: There are no ethical concerns. The results will be used to inform colorectal screening interventions in LMICs. We will publish the findings in a peer-reviewed journal and present them at relevant conferences.